ENDOMETRITIS IN MARES DUE TO COLIFORM AND ITS SUCCESSFUL TREATMENT - ASSAD, NAFIS I; PANDEY, ANAND KUMAR (The Indian Journal of Animal Reproduction, 2023)
Five broodmares with history of persistent endometritis and repeat breeding for last two breeding seasons were examined for their reproductive health by ultrasonography and the uterine samples were aseptically collected using low-volume flush technique by two-way Foley’s catheter. The uterine samples were found positive for Escherichia coll upon culture. The mares were treated with a treatment regimen consisting of uterine lavage with normal saline+ Cloprostenol (250μg, i.m.) + intrauterine antibiotic infusion based on the antibiotic sensitivity test. All mares revealed absence of uterine exudates and/or uterine wall thickening upon post-treatment ultrasound. The mares conceived after the treatment, four in the 1st artificial insemination (Al) and other in 2nd Al.